Modern Tendencies of Children's Rights Protection - Ganiev Shavkat Hamrokulovich (International Journal of Human Computing Studies, 2023)
This article provides an overview of the most recent reforms to protect the rights of children in our national legal system. It describes modern trends in the implementation of international legal agreements and protocols on the protection of children's rights into the national legal system, the protection of motherhood and childhood by the state, the protection of motherhood and childhood by the state.